2021
DOI: 10.1101/2021.07.03.21259961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of black fungus fear during the COVID-19 pandemic among the Bangladeshi health workers: a cross-sectional study

Abstract: Background: Raised of mucormycosis or black fungus cases middle of the COVID-19 pandemic, fear associated with black fungus may turn out to be a terrifying public health issue. This study aimed to assess the association between the fear and knowledge of black fungus and other determinants among healthcare workers in Bangladesh. Methods: From 25th May 2021 to 5th June 2021, a cross-sectional study was carried out among healthcare workers. For data collection during the COVID-19 pandemic, a semi-structured on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Most people are frequently exposed to Mucorales without developing the disease. Mucormycosis is generally spread by breathing in, eating food contaminated by, or getting spores of molds of the Mucorales type in an open wound (Hasan et al, 2021). So this study aims to assess women awareness regarding prevention of mucormycosis among their families Regarding socio-demographic characteristics of the studied women, the current study result showed that less than half of the studied women had an age group from 21-30 years with mean±SD of 28.72±5.53, about two thirds of them were married and from rural areas respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most people are frequently exposed to Mucorales without developing the disease. Mucormycosis is generally spread by breathing in, eating food contaminated by, or getting spores of molds of the Mucorales type in an open wound (Hasan et al, 2021). So this study aims to assess women awareness regarding prevention of mucormycosis among their families Regarding socio-demographic characteristics of the studied women, the current study result showed that less than half of the studied women had an age group from 21-30 years with mean±SD of 28.72±5.53, about two thirds of them were married and from rural areas respectively.…”
Section: Discussionmentioning
confidence: 99%
“…org/10.5281/zenodo.10928565. 23 This project contains the following underlying data: 1. data.xlsx. 2.…”
Section: Ethical Approval and Consentmentioning
confidence: 99%
“…Zenodo: Checklist for Determinants of Disease Progression in Bangladeshi COVID-19 Patients: A Cross-sectional Survey, https://doi.org/10.5281/zenodo.10928565. 23…”
Section: Ethical Approval and Consentmentioning
confidence: 99%